Tiroides Lingual : Reporte de dos casos (2000)
ABSTRACT: The thyroid gland has an important function in th body due to its hormonal action in tissue and celular growth ripen and normal function. The thyroid anlage must migrate downward during embryogenesis to allow fusion of the lateral prominences of the tongue and, if these fails, it’s trapped in tongue base. Two cases are reported in child’s aged four and eleven, who presented with a visible mass in the posterior view of the tongue, diagnosed as a lingual thyroid, confirmed with Thyroid gammagraphy.